HUBUNGAN PRAKTIK GOOD CORPORATE GOVERNANCE (GCG) DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN: PERAN MEDIASI MANAJEMEN LABA - Tubastuvi, Naelati; Wulan, Zani Nawang; Innayah, Maulida Nurul; Kharismasyah, Alfato Yusnar (AKUNTANSI DEWANTARA, 2024)
This research aims to examine the influence of Good Corporate Governance and Good Corporate Governance on Financial Performance with Profit Management as a mediating variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. This research sample consists of 33 companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022. The data used in this research was sample selection using the purposive sampling method. The analysis model uses partial analysis and path analysis. The results of this research show that GCG mechanisms have a positive effect on earnings management, CSR has a negative effect on earnings management, GCG mechanisms have no effect on financial performance, CSR has no effect on financial performance, earnings management has no effect. on performance. financial performance, earnings management cannot mediate the influence of GCG mechanisms on financial performance, and earnings management cannot mediate the influence of CSR on financial performance.